Critical discourse analysis of Indonesia Lawyer Club Talk Show (allegedly infiltrated by terrorists, why should MUI disband) - Ahmad, Yousef Bani; Rafli, Zainal; Anwar, Miftahulkhairah (Research and Innovation in Language Learning, 2023)
The researchers took one theme of the Indonesian Lawyer Club (ILC) takshow conversation, namely "Allegedly Infiltrated by Terrorists, Why Should MUI Disband." The purpose of this research is to examine and analyze the macro, super and micro structure based on Van Dijk's theory in the spoken discourse of the speakers. This study used a qualitative descriptive design. In collecting data, the researcher carried out five stages. The first is watching the ILC talk show, the second is recording relevant discourse data, the third is marking the data included in the focus and sub-focus of the research, the fourth is describing, and the fifth is verifying the data to be analyzed. Data analysis in this study used qualitative data analysis procedures based on the interactive model of Milles (1992:16). The results of this study indicate that the macro structure (theme) in the ILC program has a theme that becomes a big issue in the community. The super structure is very relevant starting from the opening, content and closing, the micro structure both from the semantics of the discourse can not be separated from the MUI being infiltrated by terrorism, the stylistics of the speakers are very varied and the rhetoric.